Goosebumps horrorland: who's your mummy? (New York: Scholastic, 2009)
Abby and Peter are staying with Uncle Jonathan in an eerie old village. Their uncle knows a lot about Egypt, and his living room even looks like an ancient tomb. Do other secrets lurk inside the house? MUM's the word! Next, Abby and Peter will get all wrapped up in a terrifying mystery. Slappy the Dummy and other villains have been sighted in HorrorLand theme park. A monster named Byron might offer help... if they can find him.